Laparoscopic hernias - Bemporad, Joshua (1999)
Laparoscopic operations are becoming more common and replacing more traditional surgical procedures. As a result, radiologists should be aware of some of the unique complications that may occur from these types of procedures. We report two cases of incarcerated bowel hernias in lateral trocar sites.